Icelandic community pharmacists' and pharmacy students' expectations of future role extensions and education requirements: a cross sectional survey. - Weidmann, Anita Elaine; Gubjrnsdttir, Unnur Karen; Gunnarsdttir, Anna Ingibjrg; Gunnarsson, Ptur; Jnsdttir, Freyja (Pharmacy Education, 2021)
Aim: To explore the expectations of Icelandic community pharmacists and final year pharmacy students on future role extensions and associated education needs. Methods: All community pharmacists across Iceland registered with the Pharmaceutical Society of Iceland (LFI) (n=136) and all fourth- and fifth-year pharmacy students enrolled at the Faculty of Pharmaceutical Sciences at the University of Iceland (n=69). An online cross-sectional questionnaire was designed, validated, piloted and analysed using descriptive statistics, logistic regression and content analysis. Results: The response rate was 27.9% (n=38) for community pharmacists and 33.3% (n=23) for fourth- and fifth-year pharmacy students respectively. Of these, 90.2% (n=55) saw the need for community pharmacists’ role extensions and most (n=60, 98.4%) were willing to accept additional education to make role extensions in Iceland possible. Logistic regression identified that students identified the need for pharmacists to be making prescribing recommendations to medical healthcare professionals (p=0.023); for example 'Pharmacists should use their knowledge to give advice and collaborate with physicians and other healthcare professionals about drug therapies'. Conclusion: Both community pharmacists and pharmacy students showed a strong willingness to extend their roles in the future. It will require government support to overcome perceived barriers and to develop further education programmes.